Method for producing optical resin composition, and optical resin composition

By heat treatment of the fluoropolymer under an atmosphere with low water vapor concentration, the problem of high coloring and water absorption during the heating forming process of the optical resin composition is solved, and an optical resin composition with low water absorption and high optical properties is achieved.

CN119505040APending Publication Date: 2025-02-25NITTO DENKO CORP
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202411671650.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2019-12-04
Filing Date
2020-12-04
Publication Date
2025-02-25

AI Technical Summary

Technical Problem

When making optical components, the optical resin composition is prone to color during the heating forming process, and has high water absorption, resulting in an increase in light absorption loss.

Method used

The fluoropolymer is heat treated in an atmosphere with a water vapor concentration of 100 volppm or less, and its terminal groups are pre-decomposed, thereby inhibiting coloring and reducing water absorption.

Benefits of technology

It is realized that coloring is suppressed in the optical member and water absorption is kept sufficiently low, thereby reducing the loss of light absorption and improving optical performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
  • Figure SMS_3
    Figure SMS_3
Patent Text Reader

Abstract

Provided is a method for producing an optical resin composition which is suppressed in coloring and has sufficiently low water absorption. This method for producing an optical resin composition comprises heat treating a fluorine-containing polymer, which is obtained by polymerizing a monomer group containing a fluorine-containing compound having a carbon-carbon double bond by means of an organic peroxide, in an atmosphere in which the concentration of water vapor is 100 volppm or less. For example, in a method for producing an optical resin composition, a terminal group of a fluorine-containing polymer is thermally decomposed by heat treatment, and a low molecular weight compound resulting from the thermal decomposition is volatilized.
Need to check novelty before this filing date? Find Prior Art

Description

[0001] This application is a divisional application of an application filed on December 4, 2020, with application number 202080083361.0, and invention name “Method for producing optical resin composition and optical resin composition”. Technical Field

[0002] The present invention relates to a method for producing an optical resin composition and the optical resin composition. Background Art

[0003] Resin compositions containing fluorine-containing polymers are used in a wide range of fields as materials for optical components such as plastic optical fibers (hereinafter referred to as "POF") and exposure components. In this specification, a resin composition used as a material for an optical component is referred to as an "optical resin composition."

[0004] The fluorine-containing polymer can be produced, for example, by polymerizing a monomer group containing a fluorine-containing compound having a carbon-carbon double bond using a polymerization initiator. As a polymerization initiator for polymerizing a monomer group containing a fluorine-containing compound, an organic peroxide is generally used.

[0005] Prior art literature

[0006] Patent Literature

[0007] Patent Document 1: Japanese Patent No. 4160918 Summary of the invention

[0008] Problems to be solved by the invention

[0009] When manufacturing an optical component, the optical resin composition is heated and melted to form, but sometimes coloring occurs during the heating and forming. This coloring becomes particularly significant when a block-shaped optical resin composition is heated and melted. According to the research of the present inventors, the cause of the coloring of the optical resin composition is the terminal group of the fluorine-containing polymer from the polymerization initiator.

[0010] The present inventors conducted further research based on this knowledge and found that if the terminal groups of the fluorinated polymer are decomposed in advance, the coloring of the optical resin composition can be suppressed, while the water absorption of the optical resin composition is increased. It should be noted that in the field of optical components, it is known that water increases the absorption loss of light (for example, Patent Document 1).

[0011] Therefore, an object of the present invention is to provide a method for producing an optical resin composition in which coloration is suppressed and water absorption is sufficiently low.

[0012] Means for solving problems

[0013] The present invention provides a method for producing an optical resin composition, comprising:

[0014] A fluorine-containing polymer obtained by polymerizing a monomer group including a fluorine-containing compound having a carbon-carbon double bond with an organic peroxide is heat-treated in an atmosphere having a water vapor concentration of 100 volppm or less.

[0015] Effects of the Invention

[0016] According to the present invention, it is possible to provide a method for producing an optical resin composition in which coloration is suppressed and water absorption is sufficiently low. DETAILED DESCRIPTION

[0017] Hereinafter, embodiments of the present invention will be described, but the following description is not intended to limit the present invention to the specific embodiments.

[0018] The method for producing an optical resin composition of the present embodiment includes: heat-treating a fluorinated polymer obtained by polymerizing a monomer group containing a fluorinated compound having a carbon-carbon double bond using an organic peroxide in an atmosphere having a water vapor concentration of 100 volppm or less. In this specification, the fluorinated polymer before the heat treatment is sometimes referred to as "fluorinated polymer (A)", and the fluorinated polymer after the heat treatment is sometimes referred to as "fluorinated polymer (B)". The optical resin composition obtained by the production method of the present embodiment includes the fluorinated polymer (B).

[0019] The fluorinated polymer (A) before heat treatment has a terminal group derived from a polymerization initiator (organic peroxide). The terminal group is, for example, an ester group. As described later, the fluorinated compound has, for example, a carbon-carbon double bond at the terminal, and all hydrogen atoms bonded to the carbon atoms constituting the double bond are substituted with fluorine atoms. The terminal group of the terminal group of the fluorinated polymer (A) formed by the fluorinated compound is, for example, represented by the following formula (4).

[0020]

Chemical formula 1

[0021]

[0022] In formula (4), R i It is determined according to the structure of the organic peroxide, and is, for example, a hydrocarbon group having 1 to 12 carbon atoms. i The hydrogen atoms contained in the hydrocarbon group may be substituted by fluorine atoms. i The hydrocarbon group may contain an aromatic ring. For example, when perfluorobenzoyl peroxide is used as the organic peroxide, R i It should be noted that "perfluoro" means that all hydrogen atoms bonded to carbon atoms are substituted with fluorine atoms.

[0023] When the fluorinated polymer (A) is heat-treated, the terminal groups of the fluorinated polymer (A) are thermally decomposed. As an example, for the terminal groups represented by the formula (4), a decomposition reaction represented by the following formula (5a) occurs.

[0024]

Chemical formula 2

[0025]

[0026] Thus, in the manufacturing method of this embodiment, the terminal group of the fluorinated polymer (A) can be changed to a functional group represented by the following formula (1) by heat treatment. In other words, the fluorinated polymer (B) after heat treatment has a terminal group represented by the following formula (1). It should be noted that the terminal group represented by the following formula (1) in the fluorinated polymer (B) can be determined by carbon 13 nuclear magnetic resonance spectroscopy ( 13 C-NMR) to confirm.

[0027]

Chemical formula 3

[0028]

[0029] The concentration of water vapor in the atmosphere during the heat treatment may be 100 volppm or less, preferably 50 volppm or less. The atmosphere during the heat treatment preferably does not contain substantially any water vapor, but the concentration of water vapor may be 0.1 volppm or more.

[0030] The components contained in the atmosphere during the heat treatment are not particularly limited, preferably containing an inert gas as the main component, and more preferably consisting essentially of an inert gas. In this specification, "containing an inert gas as the main component" means that the atmosphere contains the most inert gas on a weight basis. "Substantially consisting of an inert gas" means that the content of the inert gas in the atmosphere is 95wt% or more, preferably 99wt% or more. As inert gases, for example, nitrogen and argon can be cited, preferably nitrogen. The atmosphere during the heat treatment is preferably substantially composed of nitrogen. The heat treatment can be carried out under a reduced pressure atmosphere or a vacuum atmosphere.

[0031] The temperature of the heat treatment is not particularly limited as long as the thermal decomposition of the terminal groups of the fluorinated polymer (A) is carried out, and is, for example, 100°C or more and 400°C or less, preferably 200°C or more and 350°C or less. The time of the heat treatment is also not particularly limited, and is, for example, 50 minutes or more, and may be 250 minutes or more. The time of the heat treatment may be 1500 minutes or less. The fluorinated polymer (A) may or may not melt due to the heat treatment. Before the heat treatment, the shape of the fluorinated polymer (A) is not particularly limited, and is, for example, powdery.

[0032] The production method of this embodiment further comprises, for example, reacting a low molecular weight compound (for example, R i -C(=O)-F) from the optical resin composition. The method for removing low molecular weight compounds from the optical resin composition is not particularly limited. For example, the low molecular weight compounds can be volatilized by appropriately setting the conditions of the above-mentioned heat treatment (temperature, time, etc.), thereby removing the low molecular weight compounds from the optical resin composition. In other words, in the manufacturing method of the present embodiment, the terminal groups of the fluoropolymer (A) can be thermally decomposed by the above-mentioned heat treatment, and the low molecular weight compounds produced by the thermal decomposition can be volatilized. In the case where the fluoropolymer (A) is melted by the above-mentioned heat treatment, if the height of the liquid level of the molten fluoropolymer (A) is less than 1 mm, the low molecular weight compounds produced by the thermal decomposition are easy to volatilize. In the optical resin composition, the weight concentration of the low molecular weight compounds generated by the thermal decomposition of the terminal groups of the fluoropolymer (A) is, for example, less than 1%.

[0033] As described above, in the manufacturing method of the present embodiment, the terminal groups of the fluorinated polymer (A) derived from the organic peroxide are thermally decomposed by heat treatment. That is, the fluorinated polymer (B) contained in the optical resin composition has almost no terminal groups derived from the organic peroxide. Therefore, at the stage of heating the optical resin composition to form an optical component, low molecular weight compounds are hardly generated due to the thermal decomposition of the terminal groups derived from the organic peroxide. According to the research of the inventors, if low molecular weight compounds are generated at the stage of heating the optical resin composition to form an optical component, there is a tendency for the optical resin composition to be colored. According to the manufacturing method of the present embodiment, the above-mentioned low molecular weight compounds can be removed in advance, thereby obtaining an optical resin composition with suppressed coloring.

[0034] In addition, in the manufacturing method of the present embodiment, the heat treatment is carried out in an atmosphere with a water vapor concentration of less than 100 volppm. Therefore, it is possible to suppress further hydrolysis of the terminal group of the fluorinated polymer (B) during the heat treatment. Assuming that the terminal group represented by formula (1) is hydrolyzed, a carboxyl group is formed by the reaction represented by the following formula (5b). Functional groups containing OH groups such as carboxyl groups tend to increase the water absorption of the optical resin composition. According to the manufacturing method of the present embodiment, since the hydrolysis of the terminal group of the fluorinated polymer (B) is suppressed, the increase in the water absorption of the optical resin composition can be suppressed, and the water absorption can be maintained at a sufficiently low state.

[0035]

Chemical formula 4

[0036]

[0037] It should be noted that if a functional group including an OH group such as a carboxyl group is formed, the density fluctuation within the molecule increases in the fluorinated polymer. The density fluctuation within the molecule may cause light scattering. In the production method of this embodiment, the increase in density fluctuation within the molecule is suppressed by suppressing the hydrolysis of the terminal group of the fluorinated polymer (B), thereby suppressing the increase in light scattering caused by the optical resin composition.

[0038] [Fluorinated compounds]

[0039] The fluorinated compound contained in the monomer group is not particularly limited as long as it contains a carbon-carbon double bond and a fluorine atom. From the viewpoint of suppressing the light absorption caused by the expansion and contraction energy of the C-H bond, the fluorinated compound preferably does not substantially contain hydrogen atoms, and it is particularly preferred that all hydrogen atoms bonded to carbon atoms are replaced by fluorine atoms. In this specification, the fluorinated compound does not substantially contain hydrogen atoms means that the content of hydrogen atoms in the total amount of the fluorinated compound contained in the monomer group is less than 1 mol %.

[0040] The carbon-carbon double bond contained in the fluorine-containing compound is preferably located at the terminal of the fluorine-containing compound. In addition, it is preferred that all hydrogen atoms bonded to the carbon atoms constituting the double bond are substituted with fluorine atoms.

[0041] The fluorinated compound preferably has a fluorinated aliphatic ring structure. The fluorinated compound may have a polymerizable double bond between a carbon atom constituting a ring and a carbon atom not constituting a ring, or may have a polymerizable double bond between two carbon atoms constituting a ring. As a fluorinated compound having a polymerizable double bond between a carbon atom constituting a ring and a carbon atom not constituting a ring, for example, a fluorinated compound having a 1,3-dioxolane structure such as perfluoro-2-methylene-4-methyl-1,3-dioxolane can be cited. As a fluorinated compound having a polymerizable double bond between two carbon atoms constituting a ring, for example, a fluorinated compound having a 1,3-dioxolane structure such as perfluoro-4-methyl-1,3-dioxole and perfluoro-4-methyl-1,3-dioxole can be cited.

[0042] The fluorine-containing compound can be obtained by a known production method, for example, as typified by the production method disclosed in JP-A-2007-504125. Examples of the fluorine-containing compound having a fluorine-containing alicyclic structure include compounds represented by the following formula (2).

[0043]

Chemical formula 5

[0044]

[0045] In formula (2), R ff 1 ~R ff 4Each independently represents a fluorine atom, a perfluoroalkyl group having 1 to 7 carbon atoms, or a perfluoroalkyl ether group having 1 to 7 carbon atoms. ff 1 and R ff 2 The perfluoroalkyl groups may be connected to form a ring. In formula (2), the number of carbon atoms in the perfluoroalkyl group is preferably 1 to 5, more preferably 1 to 3, and even more preferably 1. The perfluoroalkyl group may be linear or branched. Examples of the perfluoroalkyl group include trifluoromethyl, pentafluoroethyl, and heptafluoropropyl.

[0046] In formula (2), the number of carbon atoms in the perfluoroalkyl ether group is preferably 1 to 5, and more preferably 1 to 3. The perfluoroalkyl ether group may be linear or branched. Examples of the perfluoroalkyl ether group include perfluoromethoxymethyl and the like.

[0047] R ff 1 and R ff 2 When the rings are connected to form a ring, the ring may be a 5-membered ring or a 6-membered ring. Examples of the ring include a perfluorotetrahydrofuran ring, a perfluorocyclopentane ring, and a perfluorocyclohexane ring.

[0048] Specific examples of the compound represented by the above formula (2) include compounds represented by the following formulas (M1) to (M8).

[0049]

Chemical formula 6

[0050]

[0051] The compound represented by formula (2) is preferably a compound represented by formula (M2) among the compounds represented by formulas (M1) to (M8), that is, a compound represented by the following formula (3).

[0052]

Chemical formula 7

[0053]

[0054] The fluorinated compound contained in the monomer group may be one kind or two or more kinds. That is, the fluorinated polymer (A) may be a fluorinated polymer obtained by homopolymerizing one kind of fluorinated compound or a fluorinated copolymer obtained by copolymerizing two or more kinds of fluorinated compounds.

[0055] The fluorinated polymer (A) may be, for example, a fluorinated copolymer obtained by copolymerizing a fluorinated compound having the above-mentioned fluorinated aliphatic ring structure (hereinafter referred to as the fluorinated compound (a)) with another fluorinated compound other than the fluorinated compound (a). Examples of the other fluorinated compound other than the fluorinated compound (a) include the following fluorinated compounds (b) to (d).

[0056] The fluorine-containing compound (b) is a fluorine-containing vinyl ether such as perfluorovinyl ether. The fluorine-containing vinyl ether is represented by, for example, the following formula (6).

[0057]

Chemical formula 8

[0058]

[0059] In formula (6), R 1 ~R 3 Each independently represents a fluorine atom or a perfluoroalkyl group having 1 to 7 carbon atoms. 4 It represents a perfluoroalkyl group having 1 to 7 carbon atoms. The perfluoroalkyl group may have a ring structure. A part of the fluorine atoms may be substituted by a halogen atom other than a fluorine atom. A part of the fluorine atoms in the perfluoroalkyl group may be substituted by a halogen atom other than a fluorine atom.

[0060] The fluorine-containing compound (c) is a fluorine-containing olefin such as tetrafluoroethylene and chlorotrifluoroethylene. The fluorine-containing olefin is represented by the following formula (7), for example.

[0061]

Chemical formula 9

[0062]

[0063] In formula (7), R 5 ~R 8 Each independently represents a fluorine atom or a perfluoroalkyl group having 1 to 7 carbon atoms. The perfluoroalkyl group may have a ring structure. A portion of the fluorine atoms may be substituted by a halogen atom other than a fluorine atom. A portion of the fluorine atoms in the perfluoroalkyl group may be substituted by a halogen atom other than a fluorine atom.

[0064] The fluorine-containing compound (d) is a fluorine-containing compound which has two or more polymerizable double bonds and is capable of cyclopolymerization. The fluorine-containing compound (d) is represented, for example, by the following formula (8).

[0065]

Chemical formula 10

[0066]

[0067] In formula (8), Z represents an oxygen atom, a single bond, or -OC(R 19 R 20 )O-,R 9 ~R 20Each independently represents a fluorine atom, a perfluoroalkyl group having 1 to 5 carbon atoms, or a perfluoroalkoxy group having 1 to 5 carbon atoms. A portion of the fluorine atoms may be substituted by a halogen atom other than a fluorine atom. A portion of the fluorine atoms in the perfluoroalkyl group may be substituted by a halogen atom other than a fluorine atom. A portion of the fluorine atoms in the perfluoroalkoxy group may be substituted by a halogen atom other than a fluorine atom. s and t each independently represent an integer from 0 to 5, and s+t is an integer from 1 to 6 (wherein Z is -OC(R 19 R 20 )O-, s+t can be 0).

[0068] As the fluorine-containing compound (d), a fluorine-containing compound represented by the following formula (9) can be used. The fluorine-containing compound represented by the following formula (9) is the case where Z is an oxygen atom, s is 0, and t is 2 in the above formula (8).

[0069]

Chemical formula 11

[0070]

[0071] In formula (9), R 141 , R 142 , R 151 and R 152 Each independently represents a fluorine atom, a perfluoroalkyl group having 1 to 5 carbon atoms, or a perfluoroalkoxy group having 1 to 5 carbon atoms. A portion of the fluorine atoms may be substituted by a halogen atom other than a fluorine atom. A portion of the fluorine atoms in the perfluoroalkyl group may be substituted by a halogen atom other than a fluorine atom. A portion of the fluorine atoms in the perfluoroalkoxy group may be substituted by a halogen atom other than a fluorine atom.

[0072] Specific examples of the fluorine-containing compound (d) include the following compounds.

[0073] CF2=CFOCF2CF=CF2

[0074] CF2=CFOCF(CF3)CF=CF2

[0075] CF2=CFOCF2CF2CF=CF2

[0076] CF2=CFOCF2CF(CF3)CF=CF2

[0077] CF2=CFOCF(CF3)CF2CF=CF2

[0078] CF2=CFOCFClCF2CF=CF2

[0079] CF2=CFOCCl2CF2CF=CF2

[0080] CF2=CFOCF2OCF=CF2

[0081] CF2=CFOC(CF3)2OCF=CF2

[0082] CF2=CFOCF2CF(OCF3)CF=CF2

[0083] CF2=CFCF2CF=CF2

[0084] CF2=CFCF2CF2CF=CF2

[0085] CF2=CFCF2OCF2CF=CF2

[0086] CF2=CFOCF2CFClCF=CF2

[0087] CF2=CFOCF2CF2CCl=CF2

[0088] CF2=CFOCF2CF2CF=CFCl

[0089] CF2=CFOCF2CF(CF3)CCl=CF2

[0090] CF2=CFOCF2OCF=CF2

[0091] CF2=CFOCCl2OCF=CF2

[0092] CF2=CClOCF2OCCl=CF2

[0093] [Monomer group]

[0094] The monomer group preferably contains the above-mentioned fluorine-containing compound as a main component, and more preferably consists essentially of the fluorine-containing compound. The monomer group may further contain other polymerizable compounds other than the fluorine-containing compound.

[0095] [Organic peroxide]

[0096] In the manufacturing method of the present embodiment, the organic peroxide functions as a polymerization initiator of the monomer group. The organic peroxide preferably comprises a diacyl peroxide or a peroxyester, and more preferably comprises a diacyl peroxide. The organic peroxide is preferably fluorinated. The organic peroxide more preferably does not substantially contain hydrogen atoms and is perfluorinated. Here, the organic peroxide does not substantially contain hydrogen atoms, which means that the proportion of hydrogen atoms contained is less than 1 mol % relative to the total amount of the organic peroxide used. A preferred example of the organic peroxide is perfluorobenzoyl peroxide.

[0097] [Method for producing fluorinated polymer (A)]

[0098] The fluorinated polymer (A) can be produced by polymerizing the above monomer group using the above organic peroxide. As the polymerization method, a known polymerization method can be used. For example, the above monomer group can be subjected to free radical polymerization by a conventional method to produce the fluorinated polymer (A).

[0099] [Fluoropolymer]

[0100] As described above, the fluorinated polymers (A) and (B) have terminal groups different from each other. The structure of the fluorinated polymer (A) may be the same as that of the fluorinated polymer (B) except for the terminal groups. The structural units common to the fluorinated polymers (A) and (B) are described below.

[0101] The fluorine-containing polymer includes, for example, a structural unit (a) represented by the following formula (10). The structural unit (a) is derived from the above-mentioned fluorine-containing compound (a). In the formula (10), R ff 1 ~R ff 4 Same as formula (2).

[0102]

Chemical formula 12

[0103]

[0104] Specific examples of the structural unit (a) include structural units represented by the following formulae (a1) to (a8).

[0105]

Chemical formula 13

[0106]

[0107] The structural unit (a) is preferably a structural unit (a2) among the structural units represented by the above formulae (a1) to (a8), that is, a structural unit represented by the following formula (11).

[0108]

Chemical formula 14

[0109]

[0110] The fluorinated polymer may contain one or more structural units (a). In the fluorinated polymer, the content of the structural unit (a) is preferably 20 mol% or more, more preferably 40 mol% or more, relative to the total of all structural units. By containing 20 mol% or more of the structural unit (a), the fluorinated polymer tends to have higher heat resistance. In the case of containing 40 mol% or more of the structural unit (a), in addition to high heat resistance, the fluorinated polymer also tends to have higher transparency and high mechanical strength. In the fluorinated polymer, the content of the structural unit (a) is preferably 95 mol% or less, more preferably 70 mol% or less, relative to the total of all structural units.

[0111] The fluorinated polymer may further contain other structural units in addition to the structural unit (a). Examples of the other structural units include the following structural units (b) to (d).

[0112] The structural unit (b) is represented by the following formula (12). The structural unit (b) is derived from the above-mentioned fluorine-containing compound (b). In the formula (12), R 1 ~R 4 Same as formula (6).

[0113]

Chemical formula 15

[0114]

[0115] The fluorinated polymer may contain one or more structural units (b). In the fluorinated polymer, the content of the structural unit (b) is preferably 5 to 10 mol % relative to the total of all structural units. The content of the structural unit (b) may be 9 mol % or less, or 8 mol % or less.

[0116] The structural unit (c) is represented by the following formula (13). The structural unit (c) is derived from the above-mentioned fluorine-containing compound (c). In the formula (13), R 5 ~R 8 Same as formula (7).

[0117]

Chemical formula 16

[0118]

[0119] The fluorinated polymer may contain one or more structural units (c). In the fluorinated polymer, the content of the structural unit (c) is preferably 5 to 10 mol % relative to the total of all structural units. The content of the structural unit (c) may be 9 mol % or less, or 8 mol % or less.

[0120] The structural unit (d) is represented by the following formula (14). The structural unit (d) is derived from the above-mentioned fluorine-containing compound (d). In the formula (14), Z, R 9 ~R 18 , s and t are the same as those in formula (8).

[0121]

Chemical formula 17

[0122]

[0123] The structural unit (d) is preferably represented by the following formula (15). The structural unit (d) represented by the following formula (15) is derived from the fluorine-containing compound represented by the formula (9). In the formula (15), R 141 , R 142 , R 151and R 152 Same as formula (9).

[0124]

Chemical formula 18

[0125]

[0126] The fluorinated polymer may contain one or more structural units (d). In the fluorinated polymer, the content of the structural unit (d) is preferably 30 to 67 mol% relative to the total of all structural units. The content of the structural unit (d) is, for example, 35 mol% or more, 60 mol% or less, or 55 mol% or less.

[0127] The fluorinated polymer may further contain other structural units other than the structural units (a) to (d), but preferably does not substantially contain other structural units other than the structural units (a) to (d). It should be noted that the fluorinated polymer does not substantially contain other structural units other than the structural units (a) to (d) means that the total amount of the structural units (a) to (d) is 95 mol% or more, preferably 98 mol% or more, relative to the total amount of all structural units in the fluorinated polymer.

[0128] The glass transition temperature (Tg) of the fluorinated polymer is not particularly limited, and is, for example, 100°C to 140°C, may be 105°C or higher, or may be 120°C or higher. In this specification, Tg refers to the midpoint glass transition temperature (Tg) determined in accordance with the provisions of Japanese Industrial Standards (JIS) K7121:1987. mg ).

[0129] [Optical resin composition]

[0130] The optical resin composition obtained by the production method of the present embodiment contains the fluorinated polymer (B), and preferably consists essentially of the fluorinated polymer (B). The optical resin composition may further contain additives such as a refractive index adjuster.

[0131] As described above, according to the manufacturing method of the present embodiment, the hydrolysis of the terminal group of the fluorinated polymer (B) is suppressed, so the water absorption of the optical resin composition is sufficiently low. The water absorption of the optical resin composition is, for example, 0.1% or less, preferably 0.05% or less. The water absorption of the optical resin composition can be determined by the following method. First, an optical resin composition is set as a measurement sample in a commercially available moisture adsorption and desorption measuring device. Next, the measurement sample is kept at 85°C 0% RH for 600 minutes, and further kept at 85°C 85% RH for 600 minutes. At this time, if the measurement sample absorbs (moisture absorption) water vapor in the device, the weight of the measurement sample increases. The ratio of the increase in the weight of the measurement sample based on the moisture absorption treatment to the weight of the measurement sample after the moisture absorption treatment is determined as the water absorption rate.

[0132] In addition, since the water absorption of the optical resin composition is sufficiently low, the water content (water content) in the optical resin composition is also maintained at a low state. The water content of the optical resin composition is, for example, 0.1wt% or less, preferably 0.07wt% or less, and more preferably 0.05wt% or less. The lower limit of the water content of the optical resin composition is not particularly limited, and is, for example, 0.01wt%.

[0133] According to the optical resin composition obtained by the manufacturing method of the present embodiment, it is not easy to be colored when heated and formed into an optical component. In addition, since the water content of the optical resin composition is low, the absorption loss of light caused by the water contained in the optical resin composition is low. Therefore, in the case of making a molded body from an optical resin composition, the internal transmittance of the molded body is sufficiently low. As an example, the internal transmittance of a plate-like molded body with a thickness of 10 mm made from an optical resin composition to light of a wavelength of 850 nm is, for example, 98% or more, preferably 99% or more. In this specification, internal transmittance refers to the transmittance that does not include the reflection loss caused by the reflection (Fresnel reflection) of light on the surface of the molded body. The internal transmittance of the molded body can be determined according to the provisions of the Japan Optical Glass Industry Association Standard (JOGIS) 17-2012.

[0134] Example

[0135] Hereinafter, the present invention will be described in further detail with reference to Examples and Comparative Examples, but the present invention is not limited thereto.

[0136] [Fluoropolymer (A)]

[0137] First, 22.6 g of perfluoro-2-methylene-4-methyl-1,3-dioxolane (the compound represented by formula (M2)) was dissolved in 50 mL of 1,1,1,2,2,3,4,5,5,5-decafluoropentane (Vertrel XF manufactured by Chemours-Mitsui Fluoroproducts Co., Ltd.) under an argon atmosphere at room temperature (20°C ± 15°C). While maintaining the argon atmosphere, 0.155 g of perfluorobenzoyl peroxide was added to the obtained solution and stirred to mix. Next, dissolved oxygen was removed from the solution by freeze degassing. The solution was heated to 40°C with stirring and reacted for 72 hours. The obtained reaction mixture was added to 300 mL of chloroform. The precipitate produced by this operation was recovered by filtration. The filtrate obtained was a polymer of perfluoro-2-methylene-4-methyl-1,3-dioxolane (fluorinated polymer (A)). The yield of the fluorinated polymer (A) was 19.2 g, and the yield was 81.0%.

[0138] (Sample 1)

[0139] First, an aluminum foil is placed on an aluminum flat plate, and a powdered fluorinated polymer (A) is placed on the shiny surface of the aluminum foil. The flat plate is placed inside an oven, and the fluorinated polymer (A) is heat treated at 270°C for 5 hours under a nitrogen atmosphere. The nitrogen atmosphere is adjusted by feeding nitrogen into the oven at a flow rate of 1 L / min. The concentration of water vapor in the nitrogen atmosphere is 40 volppm. The fluorinated polymer (A) is melted by the heat treatment. The height of the liquid level of the molten fluorinated polymer (A) is less than 1 mm. In addition, the terminal groups of the fluorinated polymer (A) are thermally decomposed by the heat treatment, and the low molecular weight compounds generated by the thermal decomposition are volatilized. Thus, an optical resin composition of sample 1 is obtained. The optical resin composition of sample 1 cooled to room temperature is in the form of a plate with a thickness of less than 1 mm.

[0140] (Sample 2)

[0141] An optical resin composition of Sample 2 was obtained by the same method as Sample 1 except that the heat treatment time was changed to 24 hours.

[0142] (Sample 3)

[0143] An optical resin composition of Sample 3 was obtained by the same method as Sample 1 except that the heat treatment was performed in the air. The concentration of water vapor in the air was 1.4 vol %.

[0144] (Sample 4)

[0145] An optical resin composition of Sample 4 was obtained by the same method as Sample 3 except that the heat treatment time was changed to 24 hours.

[0146] [Water absorption]

[0147] The water absorption of the optical resin composition of samples 1 to 4 was measured. First, a 1 cm square sample for measurement was cut out from the optical resin composition. The sample for measurement was placed in a moisture adsorption and desorption measuring device (IGA-SORP manufactured by Hiden). Next, the sample for measurement was kept at 85°C and 0% RH for 600 minutes, and further kept at 85°C and 85% RH for 600 minutes. The ratio of the increase in weight of the sample for measurement based on the moisture absorption treatment to the weight of the sample for measurement after the moisture absorption treatment was determined as the water absorption rate. The results are shown in Table 1. It should be noted that in Table 1, 0 means that the water absorption rate is less than 0.05%. × means that the water absorption rate is greater than 0.05%.

[0148] [Internal transmittance]

[0149] For the optical resin compositions of samples 1 to 4, the internal transmittance of a plate-shaped molded body with a thickness of 10 mm made of the optical resin composition to light of a wavelength of 850 nm was determined by the following method in accordance with the provisions of JOGIS 17-2012. First, a cylinder was made of aluminum foil, and the bottom of the cylinder was blocked with a polyimide tape. The inside of the cylinder was filled with an optical resin composition. Next, the cylinder was placed in a container for making rods made of Hastelloy. The interior of the container was made into a vacuum atmosphere, and the temperature of the container was raised to 270°C over about 2 hours. After the temperature of the container reached 270°C, the container was heated at 270°C for 3 hours. Next, the optical resin composition was formed into a rod by slowly cooling the container to room temperature. The rod is a cylindrical shape with a bottom diameter of 20 mm and a thickness of 20 mm.

[0150] Next, a diamond wheel saw is used to cut a circular plate D1 with a thickness of 5 mm and a circular plate D2 with a thickness of 12 mm from the manufactured rod. Next, the circular plate D1 is arranged inside the sample cup. At this time, a carbon tape is attached to the bottom surface of the circular plate D1, and the circular plate D1 is fixed to the sample cup using the carbon tape. Next, a resin composition (EPOFIX manufactured by Struers) is filled inside the sample cup, and the resin composition is cured. Thus, a sample S1 for measurement is obtained. The sample S1 for measurement is a cylindrical shape with a bottom diameter of 25 mm and a thickness of about 5 mm.

[0151] Next, the measurement sample S1 is set on a sample holder of an automatic table grinder, and the following steps 1 to 6 are performed on the bottom surface of the measurement sample S1 on the side to which the carbon tape is attached.

[0152] Step 1: Grind with "SiC Paper #1000" to remove the carbon ribbon.

[0153] Step 2 The sample was ground for 5 minutes using "MD Sat 9 μm" manufactured by Struers.

[0154] Step 3 The sample was ground for 5 minutes using "MD Sat 6 μm" manufactured by Struers.

[0155] Step 4 The sample was ground for 10 minutes using "MD Dur 3 μm" manufactured by Struers.

[0156] Step 5 The mixture was ground for 5 minutes using "MD Nap 1 μm" manufactured by Struers.

[0157] Step 6 The mixture was ground using "MD Chem OP-S" manufactured by Struers for 5 minutes.

[0158] The bottom surface after grinding through steps 1 to 6 is protected with filter paper. Next, the measuring sample S1 is set in a plane grinding fixture, and the surface (upper surface) of the measuring sample S1 opposite to the bottom surface is ground. The grinding uses "SiC Paper #220" until the thickness of the measuring sample S1 becomes about 4 mm. At this time, the thickness of the measuring sample S1 is confirmed by a digital micrometer. Furthermore, using "SiC Paper #1000", the upper surface of the measuring sample S1 is ground until the thickness of the measuring sample S1 becomes about 3.5 mm. Furthermore, by performing the above-mentioned steps 2 to 6 on the upper surface of the measuring sample S1, a measuring sample S1 with a thickness of about 3.5 mm is obtained.

[0159] Next, by the same method as the measuring sample S1, a measuring sample S2 with a thickness of 10 mm is obtained from the circular plate D2. It should be noted that the measuring sample S2 before grinding is a cylindrical shape with a bottom diameter of 25 mm and a thickness of about 12 mm. The grinding of the upper surface of the measuring sample S2 using "SiC Paper #220" is carried out until the thickness of the measuring sample S2 becomes about 11 mm. The grinding of the upper surface of the measuring sample S2 using "SiC Paper #1000" is carried out until the thickness of the measuring sample S2 becomes about 10.5 mm.

[0160] Next, for the measurement samples S1 and S2, the spectral transmittance including the reflection loss caused by Fresnel reflection was measured according to the provisions of JIS Z8722:2009. The spectral transmittance was measured using a UV-visible near-infrared spectrophotometer UH4150 manufactured by Hitachi High-Technologies Corporation under the conditions of a measurement wavelength of 200nm to 1300nm, a sampling interval of 1nm, and a scanning speed of 600nm / min. From the obtained spectral transmittance, the internal transmittance of a plate-shaped molded body with a thickness of 10mm made from the optical resin composition to light of a wavelength of 850nm was determined based on the following mathematical formula (1). The results are shown in Table 1.

[0161]

Mathematical formula 1

[0162]

[0163] In the above mathematical formula (1), τ refers to the internal transmittance of a plate-shaped molded body with a thickness of Lmm (10mm). a is a value calculated by the following mathematical formula (2). It should be noted that in mathematical formula (2), d1 refers to the thickness (mm) of the measurement sample S1, and d2 refers to the thickness (mm) of the measurement sample S2. T1 refers to the transmittance of the measurement sample S1 to light with a wavelength of 850nm, and T2 refers to the transmittance of the measurement sample S2 to light with a wavelength of 850nm. T1 and T2 each include reflection losses based on Fresnel reflection.

[0164]

Mathematical formula learning 2

[0165]

[0166] In Table 1, ○ means that the internal transmittance determined by the above method is 98% or more. × means that the internal transmittance determined by the above method is less than 98%.

[0167]

Table 1

[0168]

[0169] As can be seen from Table 1, for the fluorinated polymer (A), the optical resin compositions of samples 1 and 2 obtained by heat treatment in an atmosphere with a water vapor concentration of 100 volppm or less have lower water absorption than the optical resin compositions of samples 3 and 4 obtained by heat treatment in an atmosphere with a water vapor concentration exceeding 100 volppm. Since the optical resin compositions of samples 1 and 2 have low water absorption and contain almost no water, the internal transmittance of a plate-shaped molded body having a thickness of 10 mm produced from the optical resin composition to light of a wavelength of 850 nm is high.

[0170] Industrial Applicability

[0171] The optical resin composition obtained by the production method of this embodiment is suitable for materials of optical members such as plastic optical fibers, optical waveguide materials, optical lenses, prisms, and photomasks, and is particularly suitable for materials of plastic optical fibers, optical waveguide materials, and optical lenses.

Claims

1. A method for producing an optical resin composition, comprising: A fluorine-containing polymer obtained by polymerizing a monomer group including a fluorine-containing compound having a carbon-carbon double bond with an organic peroxide is heat-treated in an atmosphere having a water vapor concentration of 100 volppm or less.

2. The manufacturing method according to claim 1, wherein: By the heat treatment, the terminal groups of the fluorine-containing polymer are thermally decomposed, and low molecular weight compounds generated by the thermal decomposition are volatilized.

3. The manufacturing method according to claim 1, wherein: The heat treatment changes the terminal group of the fluorine-containing polymer into a functional group represented by the following formula (1): 。 4. The manufacturing method according to claim 1, wherein: The organic peroxide comprises a diacyl peroxide or a peroxyester.

5. The manufacturing method according to claim 1, wherein: The atmosphere consisted essentially of nitrogen.

6. The manufacturing method according to claim 1, wherein: The temperature of the heat treatment is 100° C. or higher and 400° C. or lower.

7. The manufacturing method according to claim 1, wherein: The carbon-carbon double bond is located at the terminal of the fluorine-containing compound, and all hydrogen atoms bonded to the carbon atoms constituting the double bond are substituted with fluorine atoms.

8. The manufacturing method according to claim 1, wherein: The fluorine-containing compound is represented by the following formula (2): In formula (2), R ff 1 ~R ff 4 Each independently represents a fluorine atom, a perfluoroalkyl group having 1 to 7 carbon atoms, or a perfluoroalkyl ether group having 1 to 7 carbon atoms, and R ff 1 and R ff 2 Optionally linked to form a ring.

9. The manufacturing method according to claim 8, wherein: The fluorine-containing compound is represented by the following formula (3): 。

Citation Information

Patent Citations

  • Method for producing fluorine-containing 1,3-dioxolane compound, fluorine-containing 1,3-dioxolane compound, fluorine-containing polymer of fluorine-containing 1,3-dioxolane compound, and optical or electrical material using said polymer

    JP2007504125A